DESIGNING TAX ME SERVICE APPLICATIONS IN TAX CONSULTING - Joosten, Joosten; Halim, Fandi; Arianto, Jennifer; Yulinda, Cindy (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: "Tax Me" is an application engaged in tax consulting services that is run through a mobile platform. The problems that are often faced by the public, especially taxpayers, are difficulties in choosing reliable and trusted tax consultants because many tax consultants embezzle money and slow down the tax reporting process, as well as the lack of knowledge of taxpayers about all tax regulations, a complicated and frequently changing tax system, and also there are still negative public assumptions about taxes such as corruption in taxes that have been paid by taxpayers.  The "Tax Me" application was developed using the System Development Life Cycle (SDLC) system development methodology. This application was developed as a forum for tax consulting services in collaboration with the Directorate General of Taxes (DGT) institution which is able to provide transparent and reliable tax consulting services. "Tax Me" is expected to be able to provide education to taxpayers, overcome taxpayers' concerns about the tax calculation and reporting process as well as in choosing a tax consultant who can be trusted. In addition, several features of the "Tax Me" application such as: NPWP, Tax Calculation, Tax Consultation, Report & Check Annual Tax Return, E-Billing & Pay Tax, Tax Reminder and Tax Article.            Keywords: directorate general of taxes (DJP); tax; tax me; taxpayer  Abstrak: “Tax Me” adalah aplikasi yang bergerak pada bidang pelayanan konsultasi pajak yang dijalankan melalui platform mobile. Masalah yang sering dihadapi oleh masyarakat khususnya Wajib Pajak adalah kesulitan dalam memilih konsultan pajak yang dapat diandalkan dan dipercaya karena banyak konsultan pajak yang menggelapkan uang dan memperlambat proses pelaporan pajak, serta kurangnya pengetahuan Wajib Pajak mengenai segala peraturan perpajakan, sistem perpajakan yang rumit dan sering berubah, dan juga masih ada anggapan negatif masyarakat tentang pajak seperti korupsi atas pajak yang telah dibayarkan oleh Wajib Pajak. Aplikasi “Tax Me” dikembangkan dengan menggunakan metodologi pengembangan sistem System Development Life Cycle (SDLC). Aplikasi ini dikembangkan sebagai wadah layanan konsultasi perpajakan yang bekerja sama dengan lembaga Direktorat Jenderal Pajak (DJP) yang mampu memberikan layanan konsultasi perpajakan yang transparan dan terpercaya. “Tax Me” diharapkan mampu memberikan edukasi kepada Wajib Pajak, mengatasi kekhawatiran Wajib Pajak terhadap proses perhitungan dan pelaporan pajak juga dalam memilih konsultan pajak yang dapat di percaya. Disamping itu, beberapa fitur dari aplikasi “Tax Me” seperti: NPWP, Hitung Pajak, Konsultasi Pajak, Lapor & Periksa SPT Tahunan, E-Billing & Bayar Pajak, Pengingat Pajak dan Artikel Pajak. Kata kunci: direktorat jenderal pajak (DJP); pajak; tax me; wajib pajak